2022
DOI: 10.1007/s43545-022-00524-3
|View full text |Cite
|
Sign up to set email alerts
|

Professors want to share: preliminary survey results on establishing open-source-endowed professorships

Abstract: This study proposes a novel policy to provide incentives for open science: to offer open-source (OS)-endowed professorships. To hold an open-source-endowed chair , in addition to demonstrated excellence in their field, professors would need to agree to (1) ensuring all of their writing is distributed via open access in some way and (2) releasing all of their intellectual property in the public domain or under appropriate open-source licenses. The results of this survey study of universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…There is also widespread interest in vastly expanding transparency in all aspects of the scientific knowledge-generating process (European Commission, 2015). Furthermore, recent research has shown a clear willingness of academics to expand OA, which would hasten scientific progress while also making science more just and inclusive (Pearce et al, 2022a(Pearce et al, , 2022b. The results of this article indicate that functionally doing this would not be prohibitively expensive or time consuming for the past literature and would provide a legal means to provide the same level of access that Sci-Hub provides illegally (Bohannon, 2016).…”
Section: Potential Long-term Impactmentioning
confidence: 81%
“…There is also widespread interest in vastly expanding transparency in all aspects of the scientific knowledge-generating process (European Commission, 2015). Furthermore, recent research has shown a clear willingness of academics to expand OA, which would hasten scientific progress while also making science more just and inclusive (Pearce et al, 2022a(Pearce et al, , 2022b. The results of this article indicate that functionally doing this would not be prohibitively expensive or time consuming for the past literature and would provide a legal means to provide the same level of access that Sci-Hub provides illegally (Bohannon, 2016).…”
Section: Potential Long-term Impactmentioning
confidence: 81%
“…Most of the publications were indicated as research culture, perspective, commentary, essay, proceedings of a workshop, research article, world view, opinion, research note, editorial, report, and research policy (n = 22). Only three records 19,31,33 in our scoping review were empirical research. The majority of the records did not report any funding information (n = 15), but of those that mentioned if they had received funding, seven records (47%) reported receiving funding, and similarly six records (53%) reported receiving no funding.…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%